Novel homozygous in-frame deletion of GNAT1 gene causes golden appearance of fundus and reduced scotopic ERGs similar to that in Oguchi disease in Japanese family. (3rd September 2019) - Kubota, Daiki; Oishi, Noriko; Gocho, Kiyoko; Kikuchi, Sachiko; Yamaki, Kunihiko; Igarashi, Tsutomu; Takahashi, Hiroshi; Ishida, Nobuo; Iwata, Takeshi; Mizota, Atsushi; Kameya, Shuhei
ABSTRACT: Background : The GNAT1 gene encodes the alpha-subunit of transducin in rod photoreceptors and is an important part of the phototransduction cascade. Defects in GNAT1 are very rare but have been identified in autosomal dominant and recessive congenital stationary night blindness (CSNB) and autosomal recessive rod-cone dystrophy. The purpose of this study was to determine the phenotype-genotype relationship in a non-consanguineous Japanese family with a GNAT1 mutation. Methods : Detailed ophthalmic examinations were performed on the patients and their family members. Whole exome sequencing (WES) was applied to the DNA obtained from the family members. Sanger sequencing and co-segregation analyses were performed to identify the most likely pathogenic variant. Results : Two female (13- and 11-years) and one male (15-years) patients from a family had night blindness from their childhood. The fundus had a mild golden appearance regardless of the state of light- or dark-adaptation. Electroretinographic (ERG) analyses showed that the scotopic a-wave was extinguished, and the mixed rod-cone responses were severely reduced with an electronegative form in patients. The shapes of the dark-adapted ERGs were similar to those recorded from patients with Oguchi disease. We identified a homozygous in-frame deletion c.818_820delAGA, p.Lys273del in the GNAT1 gene. Variants were verified by Sanger sequencing and co-segregated with the disease in five members of the family. Conclusions : Our findings indicate that a recessive GNAT1 mutation found in this family could be the cause of the golden appearance of the fundus and negative ERGs with reduced a-waves, and nearly absent b-waves in the mixed rod-cone ERGs.